PHYSIOLOGICAL RESPONSES OF FEMALE BEEF CATTLE AGAINST PEATLAND MICROCLIMATE STRESS IN CENTRAL KALIMANTAN - Adrial, Adrial; Priyanto, Rudy; Salundik, Salundik; Yani, Ahmad; Abdullah, Luki (Universitas Syiah Kuala, 2023)
This study aimed to evaluate the physiological response of female beef cattle to peatland microclimate stress in Central Kalimantan. This study used direct observation on small holder beef cattle farm. Microclimate data on 41 units cattle barns and physiological parameters of female cattle were collected in the morning, at noon and in the afternoon. The physiological parameter measurements involved 215 female beef cattle, consisting of 119 Bali and 96 crossbred cattle with different physiological stages including pregnant cows, lactating cows, dry cows, heifers and calves. The microclimate condition within cattle barns on peatland of Central Kalimantan is not the comfort zone for beef cattle. It is characterized by high air temperature and relative humidity, and low wind speed, which result in high temperature humidity index (THI). The barn with gable roof type and asbestos materials gave the lowest THI. This Microclimate caused heat stress to beef cattle reared on the peatlands, indicated by the high rectal temperature, heart rate, respiratory rate, and heat tolerance coefficient, although it was still categorized as mild to moderate stress. Bali cattle showed better physiological responses to microclimate stress than crossbred cattle. Pregnant crossbred cows were the most susceptible to peatland microclimate stress.